Comment and Comics Artwork by Mohd Yaman Ahmad Mus in Anak Sabah Newspaper on 1957 - Rahim, Mohd Sawari; Ibrahim, Ismail; Zakaria, Suraya Hani (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2015)
The aims for producing comics in newspaper is to convey a message instead of just an entertainment for the newspaper readers. It also can be a documentation materials for historical records and civilization history through the situation at that time. These visual images are used by Mohd Yaman Ahmad Mus to display the true story about the behavior, attitudes and moral values that apply in everyday life through his creativity and self-expression. This aims to teach and create awareness among public besides of building a harmony and well-being of the community. The display image was analyzed using a theoretical approach of iconography by Erwin Panofsky (1955). This theory was classified into three levels, which is pre-iconographic, iconography and iconological (iconology interpretation) to explain and demystify the nature and meaning of painting in a holistic manner. The study showed that the content of messages and lessons in painting shows road safety issues which are still happen since the pre-independence era in Sabah until now.